Hepatitis B surface antigen (HbsAg) in blood and gential secretions of paients with sexually transmitted diseases in Ibadan, Nigeria. (2005)
A total of 100 patients attending the Special Treatment Clinic of the University Teaching Hospital (UCH), Ibadan between October, 1998 and April, 1999 were studied to detect Hepatitis B surface antigen (HbsAg) in the blood and genital discharges. This was with a view of establishing whether infected persons (positive by blood test) also excrete the antigen, HbsAg, in their genital secretions. Urethral swabs were collected from 63 male patients, while High Vaginal and Endocervical swabs were collected from 37 female patients. Blood samples were collected from all the patients. HbsAg was tested for by Enzyme immunoassay technique with Wellcozyme HbsAg kit. Of the 63 male patients, 10 (15.9%) had HbsAg in the urethral secretion while 22 (34.9%) had it in their blood, 70% of these male patients were within the age range 11-30 years. Of the 37 female patients, 34 (92%) had HbsAg in the Endocervical secretions, 6 (16.2%) of them had HbsAg in their blood. Eighty percent of the female patients with positive HbsAg in the genital secretions were within age range 21-40 years. This study documents that Hepatitis B virus can be transmitted sexually in this environment